2013
DOI: 10.1017/sjp.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Psychoticism and Disruptive Behavior can be also Good Predictors of School Achievement

Abstract: The relations of Gf (Standard Progressive Matrices Raven), Gc (verbal scale of Wechsler Intelligence Scale for Children-Third Version), personality dimensions (Eysenck Personality Questionnaire-Junior Version), and disruptive behavior (TDAH scale) with school achievement (measured by TDE test and PISA test) were investigated. Two samples of students (total N = 534) representing a broad range of socioeconomic status (SES) participated in this study. Path models were conducted. The results demonstrated that (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…In contrast, Schubiger et al (2015) found that male marmosets ( Callithrix jacchus ) showing higher emotional reactivity towards the experimenter (i.e., highly neurotic individuals) were less likely to participate in cognitive tasks, but this did not affect their performance. In humans, higher Neuroticism and higher Psychoticism have been repeatedly linked to poorer performance, both in academic ( Chamorro-Premuzic & Furnham, 2003 ; Flores-Mendoza et al, 2013 ; Poropat, 2011 ) and non-academic contexts ( Dobson, 2000 ; Reynolds, McClelland & Furnham, 2014 ), and especially under stressful conditions ( Byrne, Silasi-Mansat & Worthy, 2015 ). Nonetheless, Eysenck (1981) suggested that the relationship between Neuroticism and performance depends on the intelligence of the subject: higher Neuroticism is related to higher academic achievement in more intelligent individuals, who are better able to cope with anxiety, while the opposite pattern is observed for less intelligent subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Schubiger et al (2015) found that male marmosets ( Callithrix jacchus ) showing higher emotional reactivity towards the experimenter (i.e., highly neurotic individuals) were less likely to participate in cognitive tasks, but this did not affect their performance. In humans, higher Neuroticism and higher Psychoticism have been repeatedly linked to poorer performance, both in academic ( Chamorro-Premuzic & Furnham, 2003 ; Flores-Mendoza et al, 2013 ; Poropat, 2011 ) and non-academic contexts ( Dobson, 2000 ; Reynolds, McClelland & Furnham, 2014 ), and especially under stressful conditions ( Byrne, Silasi-Mansat & Worthy, 2015 ). Nonetheless, Eysenck (1981) suggested that the relationship between Neuroticism and performance depends on the intelligence of the subject: higher Neuroticism is related to higher academic achievement in more intelligent individuals, who are better able to cope with anxiety, while the opposite pattern is observed for less intelligent subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Conscientious individuals tend to be more goal-oriented and plan more, and they are better able to delay gratification (Roberts et al, 2009). Furthermore, according to several studies, Conscientiousness in the FFM negatively correlates with Psychoticism in the PEN model (Eysenck, 1992), which would explain the negative impact of Psychoticism on academic performance (Flores-Mendoza et al, 2013;Heaven, Ciarrochi & Vialle, 2007;Poropat, 2011). However, Psychoticism has also been consistently linked to creativity (Abraham et al, 2005;Acar & Runco, 2012;Eysenck, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…8(1) con el modelo y medidas de Eysenck, porque pueden ser útiles en el psicodiagnóstico y orientación escolar, particularmente de los jóvenes adolescentes. Lo mismo piensan otros autores (e.g., Scholte y De Bruyn, 2001;López y López, 2003;Flores-Mendoza, Widaman, Mansur-Alves, Bacelar y Saldanha, 2013). De todos modos, hemos elegido el enfoque centrado en las personas, que incluye a psicoticismo dentro de un perfil clasificatorio, antes que el enfoque dimensional o centrado en las variables, quedando este último enfoque más expuesto a la crítica de Poropat (2011).…”
Section: Implicacionesunclassified
“…Also, academic achievement might be critical indicator of mental health problems (Suldo et al, 2011) and declines in school success might be serious as children enter elementary school (Blackwell et al, 2007). Therefore, the students' disruptive behaviors have detrimental effects on student academic achievement (Campbell, 1994;Mendoza et al, 2013;Pianta, 1999Pianta, , 2001Birch & Ladd, 1998). Accordingly, Pianta (1999) found that students with externalizing behavioral problems (e.g., aggression and classroom disruption) were at risk of academic failure and school dropout.…”
Section: Introductionmentioning
confidence: 99%